Radiation-induced heart disease in lung cancer radiotherapy: A dosimetric update. Issue 41 (October 2016) - Ming, Xin; Feng, Yuanming; Yang, Chengwen; Wang, Wei; Wang, Ping; Deng, Jun
Abstract: Background: Radiation-induced heart disease (RIHD), which affects the patients' prognosis with both acute and late side effects, has been published extensively in the radiotherapy of breast cancer, lymphoma and other benign diseases. Studies on RIHD in lung cancer radiotherapy, however, are less extensive and clear even though the patients with lung cancer are delivered with higher doses to the heart during radiation treatment. Methods: In this article, after extensive literature search and analysis, we reviewed the current evidence on RIHD in lung cancer patients after their radiation treatments and investigated the potential risk factors for RIHD as compared to other types of cancers. Result: Cardiac toxicity has been found highly relevant in lung cancer radiotherapy. So far, the crude incidence of cardiac complications in the lung cancer patients after radiotherapy has been up to 33%. Conclusion: The dose to the heart, the lobar location of tumor, the treatment modality, the history of heart and pulmonary disease and smoking were considered as potential risk factors for RIHD in lung cancer radiotherapy. As treatment techniques improve over the time with better prognosis for lung cancer survivors, an improved prediction model can be established to further reduce the cardiac toxicity in lung cancer radiotherapy.